Stationary phase-specific expression of dominant flocculation genes for controlled flocculation of yeast - Domingo, Jody L. (Jody Lawren) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2003.